Assessing economics of treatments for gynecological cancer where clinical effectiveness meets value for money. Issue 5 (1st August 2004) - Stoykova, B.; Dowie, R.; Kitchener, H. C.
Abstract : During the last 10 years, the management of gynecological cancer has been undergoing a great deal of change. This is due to a drive to reduce ineffective treatment and associated morbidity while at the same time maximizing the benefits of currently available treatment. The foundation for this approach has been high-quality clinical trials which have been performed in increasing numbers. These trials can provide strong evidence that treatments are equivalent or that a new drug adds superiority to previous treatment. The access that women have to the most effective forms of treatment often depends on the availability of healthcare resources and their affordability within the healthcare system. Healthcare decision makers increasingly require not just clinical effectiveness of treatments but also cost-effectiveness to be demonstrated. While health economic methods have been applied to many forms of cancer treatment and screening, there have been very few rigorous economic studies performed in gynecological cancer. This article discusses how economic analysis can be incorporated into clinical trials and how it can provide the sort of value for money determination that payers of healthcare are now requiring. Economic analysis may add a little to the cost of trials, but in the end, it may increase access to treatment by convincing decision makers of cost-effectiveness.